2015
DOI: 10.1007/s11430-015-5094-6
|View full text |Cite
|
Sign up to set email alerts
|

Crustal velocity structure in the Emeishan large igneous province and evidence of the Permian mantle plume activity

Abstract: The Emeishan large igneous province (ELIP) in SW China is interpreted to be associated with an ancient mantle plume. Most of the constraints on the role of mantle plume in the generation of the Emeishan flood basalts were provided by geological and geochemical methods, but the geophysical investigation is very limited. In order to better understand the deep structure and features of ELIP, we have studied the crustal velocity structure using the data acquired from the Lijiang-Panzhihua-Qingzhen wide-angle seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 55 publications
(83 reference statements)
4
33
0
Order By: Relevance
“…In addition, the velocity in the inner zone of the Emeishan large igneous province (LIP) is relatively higher than that in the surrounding area, which is also clearly observed by some other tomographic studies (e.g., Bao et al, ; Yao et al, ; Figure ). This high‐velocity anomaly supports the idea of residual basalts in the Permian (Xu et al, , ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the velocity in the inner zone of the Emeishan large igneous province (LIP) is relatively higher than that in the surrounding area, which is also clearly observed by some other tomographic studies (e.g., Bao et al, ; Yao et al, ; Figure ). This high‐velocity anomaly supports the idea of residual basalts in the Permian (Xu et al, , ).…”
Section: Resultssupporting
confidence: 86%
“…The center of the southern SYB shows a relatively high velocity. Previous studies have revealed the similar features of this area: high seismic velocity, low attenuation, high Vp/Vs ratios, low heat flow, and high density anomaly (Bao et al, ; Chen et al, , ; Deng et al, , ; Shen et al, ; Wei et al, ; Xu et al, ; Yang et al, ; Yao et al, ; Zhao et al, ; Figure ). These features manifest the strength of the crust in this area, which may result from the generation of the Emeishan basalts and crustal accretion during the upwelling of a mantle plume in the Permian (Chen et al, ; He et al, ).…”
Section: Resultsmentioning
confidence: 57%
“…At each station of the COMPASS-ELIP array, we first processed the available data set of RFs using the H-stacking method based on the averaged crustal P-wave velocity model (Fig. 5b) derived from the COMWIDE-ELIP experiment (Xu et al, 2015) (Fig. 5d), and estimated the standard errors of H and Vp/Vs ratio by the bootstrap method (Efron and Tibshirani, 1986) for 100 trials.…”
Section: Crustal Structure Of Elipmentioning
confidence: 99%
“…However, in this study, we used a modified model that was based on the crustal P-wave velocity ( Fig. 5b) derived from the COMWIDE-ELIP experiment (Xu et al, 2015) and the crustal Vp/Vs ratio ( Fig. 5f) from H- stacking.…”
Section: Crustal Structure Of Elipmentioning
confidence: 99%
“…In the past 30 years, several thousand kilometer sounding profiles have been established in Yunnan region (Kan and Lin, 1986;Zhang et al, 2002Zhang et al, , 2009Xu et al, 2015;Pan et al, 2015). Many other geophysical observations, such as surface wave tomographies (Hu et al, 2008;Yao et al, 2008), receiver functions (Hu et al, 2008;Wu and Zhang, 2011;C.…”
Section: Introductionmentioning
confidence: 99%